2006
DOI: 10.1073/pnas.0506589103
|View full text |Cite
|
Sign up to set email alerts
|

Arginase modulates myocardial contractility by a nitric oxide synthase 1-dependent mechanism

Abstract: Cardiac myocytes contain two constitutive NO synthase (NOS) isoforms with distinct spatial locations, which allows for isoformspecific regulation. One regulatory mechanism for NOS is substrate (L-arginine) bioavailability. We tested the hypothesis that arginase (Arg), which metabolizes L-arginine, constrains NOS activity in the cardiac myocyte in an isoform-specific manner. Arg activity was detected in both rat heart homogenates and isolated myocytes. Although both Arg I and II mRNA and protein were present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 54 publications
7
74
0
1
Order By: Relevance
“…Furthermore, reciprocal regulation of NOS by arginase has been demonstrated in cells and organs in which NO is an important signaling molecule, including the endothelium, cardiac myocytes, penis, airway, skin, and inflammatory cells [4][5][6]10,16,[29][30][31]. It was demonstrated that arginase II activity is upregulated in atherosclerosis-prone mice and is associated with impaired endothelial NO production, endothelial dysfunction, vascular stiffness, and ultimately, aortic plaque development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reciprocal regulation of NOS by arginase has been demonstrated in cells and organs in which NO is an important signaling molecule, including the endothelium, cardiac myocytes, penis, airway, skin, and inflammatory cells [4][5][6]10,16,[29][30][31]. It was demonstrated that arginase II activity is upregulated in atherosclerosis-prone mice and is associated with impaired endothelial NO production, endothelial dysfunction, vascular stiffness, and ultimately, aortic plaque development.…”
Section: Discussionmentioning
confidence: 99%
“…Arginase, which shares L-arginine as a substrate with eNOS, hydrolyzes L-arginine to ornithine and urea as part of the urea cycle. It is well recognized that arginase modulates NOS activity by regulating intracellular L-arginine bioavailability [4][5][6]. Thus, the balance between arginase and eNOS activities partly regulates vascular endothelial NO production.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, our findings clearly demonstrate for the first time a hypertensive phenotype in these mice when BP was assessed in the conscious animal by telemetry or under anesthesia by arterial catheterization. Despite recent findings that suggest that arginase II inhibition may be suitable therapy for heart failure, 25 we also demonstrated cardiac diastolic dysfunction and left ventricular hypertrophy in the arginase II KO mice as early as 15 weeks of age, suggesting that a lack of arginase II is not sufficient to preserve cardiac function in the face of sustained pressure overload. In comparison with the eNOS KO mice, where the MAP of 12-to 16-week-old mice was 15 mm Hg higher than the C57BL/6 strain, 26 the arginase II KO mice demonstrate a Ϸ25 mm Hg greater BP than age-matched C57BL/6 mice, suggesting a more fundamental role for arginase II than for eNOS in BP regulation.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, there is potential for competing subcellular colocalization between these isozyme families to contribute to their respective enzyme activities. Both arginase 1 and 2 have been implicated in regulating NOS1 activity through the depletion of intracellular L-arginine [64,65]. In cultured endothelial cells arginase 2 has been demonstrated to regulate the activity of NOS3, and this regulation has been shown to take place within non-freely exchangeable Larginine pools [66,67].…”
Section: Subcellular Localizationmentioning
confidence: 99%